Modified positive electrode material and preparation method thereof, sodium ion battery and power equipment
By diagonally replacing the elements in the positive electrode material of sodium ion battery, the cation disorder and mixing entropy of the material are improved, the problem of poor cycle stability is solved, and high capacity and excellent electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411315714.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-17
AI Technical Summary
The existing sodium ion battery positive electrode materials have poor cycle stability during charging and discharging, which leads to structural changes and irreversible phase change, affecting battery performance.
By substituting at least one element in the positive electrode material before modification by diagonal rule, replacing the corresponding elements in the positive electrode material with elements that conform to the diagonal rule, improving the cation disorder and mixing entropy, and suppressing Na+/vacancies Orderly arrangement phenomenon enhances the structural stability and electrochemical properties of the material.
The excellent cycle stability and rate performance of the modified positive electrode material are achieved, the initial discharge specific capacity is high and the capacity retention rate reaches more than 92.68% after 500 cycles, which significantly improves the electrochemical performance of sodium ion batteries.
Smart Images

Figure CN119153679A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a modified positive electrode material and a preparation method thereof, a sodium ion battery and a power device. Background Art
[0002] With the continuous development of science and technology, the traditional energy market has led to a series of environmental pollution problems. In order to reduce excessive dependence on fossil fuels, humans have turned their attention to renewable energy. In the 1970s, lithium-ion batteries and sodium-ion batteries appeared almost at the same time. Due to the limitations of sodium-ion battery energy density and cycle performance, lithium-ion batteries quickly occupied the power energy market. With the extensive research on lithium-ion batteries, people's demand for lithium resources has increased, and the scarcity of lithium resources and uneven distribution in the earth's crust have caused their costs to rise, which has brought sodium-ion batteries, which are low-cost and widely distributed, back into people's attention.
[0003] Among the existing sodium ion battery cathode materials, layered transition metal oxide materials (Na x MeO2) has the advantages of high theoretical specific capacity, high sodium ion insertion and extraction speed, and good rate performance due to its stable transition metal layer framework and two-dimensional sodium ion transport channel; however, as the charge and discharge process proceeds, this type of material will undergo Na + / hole structure rearrangement, causing phase structure transformation; large radius sodium ion migration will cause the slip of oxygen layer, causing irreversible multiphase transformation, thus affecting the diffusion of ions in the bulk phase and causing structural changes; in addition, Mn 3+ and Ni 3+ The Jahn-Teller effect (t 2g The high spin of orbital ions will lead to structural distortion; all of these lead to the problem of poor cycle stability of this type of material in practical applications, and it is impossible to maintain a high capacity. Current research is mainly focused on improving the structural stability of this type of positive electrode material, mainly by improving the performance of anionic oxygen-participated layered positive electrode materials through doping, coating, etc., and also by improving the overall performance of the battery through surface modification, structural design, multi-phase composite and other means.
[0004] The element doping and substitution strategy can effectively slow down the phase change process, significantly improve the structural stability of the material, and exhibit diverse sodium storage performance characteristics by optimizing the embedding and deintercalation mechanism. In addition, this method can also precisely control the interlayer spacing of the layered oxide crystal structure, effectively inhibit the occurrence of the Jahn-Teller effect, and significantly enhance the bonding strength of the TM-O bond, thereby giving the material better overall performance.
[0005] CN116259743A discloses a titanium-doped sodium ion battery positive electrode layered oxide material and a preparation method and application thereof. The chemical formula of the titanium-doped sodium ion battery positive electrode layered oxide material is Na x Ni (1-y) / 2 Mn (1-y) / 2 Ti y O2, where 0.7≤x<1, 0.01≤y<0.3; it is passed through NaNi 0.5 Mn 0.5 O2 is doped with tetravalent titanium and Mn 3+ The content of Ti 4+ The spacing between the sodium layers is enlarged, the occurrence of irreversible phase change is suppressed, and the structural stability of the material is improved.
[0006] CN117613255A discloses a layered oxide positive electrode material, a sodium ion battery and a preparation method. The chemical formula of the layered oxide positive electrode material is Na x M y Me z , wherein 0.8≤x≤1.1, the M is selected from one or more elements of Group IA and Group IIA, 0≤y≤1, the Me is selected from one or more metal elements, and 0<z≤1; by doping with certain elements, the structural stability of the layered oxide positive electrode material can be effectively improved, and the reversible capacity and cycle life of the material can be increased.
[0007] CN117878324A discloses a high-performance gradient-doped oxide positive electrode material for sodium ion batteries and a preparation method thereof. The positive electrode material is an O3-type layered oxide for sodium ion batteries, and the content of doped elements increases from the core to the surface of the material. The chemical formula of the positive electrode material is NaNi x Fe y Mn z M a O2, wherein 0<a≤0.1, 0<x<1, 0<y<1, 0<z<1, x+y+z+a=1, and M is a doping element; the concentration of the doping element gradually increases from the core of the material, thereby reducing the irreversible capacity loss of the positive electrode material of the sodium ion battery and improving the cycle stability and safety performance of the sodium ion battery.
[0008] Although the electrochemical performance of layered transition metal oxides for sodium-ion batteries has been improved to a certain extent through the strategy of element doping, there is still a lack of a universal principle for selecting doping elements to achieve the improvement of the cation disorder in the positive electrode material, maximize the mixing entropy of the material, and inhibit the Na+ at a specific sodium ion concentration. + The phenomenon of orderly arrangement of sodium ion batteries / vacancies, thereby improving material capacity and cycle stability and further enhancing the electrochemical performance of sodium ion batteries, has become a problem that needs to be solved urgently. Summary of the invention
[0009] In order to solve the above technical problems, the present invention provides a modified positive electrode material and a preparation method thereof, a sodium ion battery and a power device. The modified positive electrode material of the present invention is obtained by replacing at least one element in the positive electrode material before modification using the diagonal rule, and by replacing the corresponding element in the positive electrode material with an element that conforms to the diagonal rule, the disorder degree of cations in the modified positive electrode material is improved, the mixing entropy of the material is maximized, and the Na+ present in the material during the charge and discharge process is suppressed. + / Vacancy ordered arrangement phenomenon and irreversible phase transition phenomenon; in addition, the preparation method of the present invention is simple, and the sodium ion battery prepared by using the modified positive electrode material has excellent cycle stability and rate performance.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a modified positive electrode material, wherein the modified positive electrode material is a layered transition metal oxide material;
[0012] The modified positive electrode material is obtained by replacing at least one element in the positive electrode material before modification using the diagonal rule.
[0013] In the present invention, the diagonal rule is that, assuming that the A-position element is the element to be replaced, the B-position element adjacent to the lower right corner of the A-position element is the element to replace the A-position, that is, the A-position element and the B-position element meet the diagonal rule.
[0014] The modified positive electrode material provided by the present invention is obtained by replacing at least one element in the positive electrode material before modification using the diagonal rule, and replacing the corresponding element in the positive electrode material with a diagonal element with similar chemical properties, thereby achieving an increase in the disorder degree of cations in the modified positive electrode material, maximizing the mixing entropy of the material, and inhibiting the Na under a specific sodium ion concentration. + / The orderly arrangement of vacancies can increase the material capacity and cycle stability, and further enhance the electrochemical performance of sodium-ion batteries.
[0015] In the diagonal rule, the charge number effect and radius effect of the two elements are opposite, and they have similar ionic states and chemical properties (such as ionic radius, charge density and electronegativity, etc.), so they can replace each other, thereby increasing the mixing entropy of the material.
[0016] Furthermore, for ions with the same outermost electron configuration characteristics, their polarization degree shows a trend of increasing from left to right, and this increase is directly related to the increase in the number of charges carried by the ions. On the contrary, when examining the elements of the same main group, from the beginning to the end of the group, the ion polarization effect gradually weakens with the increase of the atomic number. This polarization trend causes the elements located in the upper left corner and the lower right corner to share similar ion potentials, and this commonality leads to their similarity in chemical properties.
[0017] On the one hand, through similar chemical properties, some diagonal elements have similar reactivity and behavior, which makes the substitution process easier, increases the disorder of the system, and thus leads to an increase in the mixing entropy of the material; on the other hand, through similar electronic structures, the diagonal elements exhibit similar bonding methods and electron transfer characteristics when participating in chemical reactions, and can combine or replace each other in various ways, making it easier for them to enter specific substitution sites.
[0018] In addition, since the properties of the elements on the diagonal are neither exactly the same nor similar, the interactions between them are more complex than those between the off-diagonal elements. This complex interaction makes the arrangement of atoms and the distribution of electrons more diverse after doping or substitution mixing, showing a trend of maximum increase in mixing entropy.
[0019] As a preferred technical solution of the present invention, the chemical formula of the positive electrode material before modification includes Na x MeO2, wherein 0<x≤1, for example, x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, etc., and the Me includes any one or a combination of at least two of the transition metal elements.
[0020] Preferably, the diagonal rule includes replacing the Na position with a Ca element located adjacent to the lower right corner of the Na element; and / or replacing at least one element in the Me position with an element located adjacent to the lower right corner of the Me element; and / or replacing the O position with a Cl element located adjacent to the lower right corner of the O element.
[0021] Preferably, the chemical formula of the modified positive electrode material includes Na x-a Ca a Me 1-b Y b O 2-c Cl c, where 0<x≤1, for example, x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.67, 0.7, 0.8, 0.9 or 1.0, etc.; 0≤a<x, 0≤b<1, for example, b can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.99, etc.; 0≤c<2, for example, c can be 0, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8 or 1.99, etc.; and a, b, c are not 0 at the same time, and Y and Me conform to the diagonal rule.
[0022] Preferably, 0.5<x≤0.7.
[0023] Preferably, 0<a≤0.5, for example, a can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5, etc., preferably 0.01≤a≤0.2.
[0024] Preferably, 0<b≤0.5, for example, b can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5, etc., preferably 0.01≤b≤0.2.
[0025] Preferably, 0<c≤0.5, for example, c can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5, etc., preferably 0.01≤c≤0.2.
[0026] Preferably, the Me includes any one of Fe, Ni, Co, Mn or V or a combination of at least two thereof, preferably a combination of Ni and Mn.
[0027] Preferably, Y includes any one of Rh, Ag, Pd, Ru or Mo or a combination of at least two thereof, preferably a combination of Ag and Ru.
[0028] Among Me and Y described in the present invention, Fe and Rh, Ni and Ag, Co and Pd, Mn and Ru, and V and Mo are elements that conform to the diagonal rule.
[0029] In a second aspect, the present invention further provides a method for preparing the modified positive electrode material according to the first aspect, the preparation method comprising the following steps:
[0030] The positive electrode material before modification is reacted with the modification source in situ to obtain a modified positive electrode material;
[0031] The modified element in the modified source and at least one element in the positive electrode material before modification conform to the diagonal rule.
[0032] As a preferred technical solution of the present invention, the reaction method includes a sol-gel method, a solid phase reaction method or a coprecipitation method, preferably a sol-gel method.
[0033] Preferably, the sol-gel method comprises the following steps:
[0034] The mixed solution and the complexing agent solution are mixed and reacted to obtain a wet gel, and after drying and calcining, the modified sodium ion battery positive electrode material is obtained;
[0035] The mixed solution comprises a sodium source, a Me source, a modification source and a solvent.
[0036] The molar ratio of the sodium source, Me source and modified source in the mixed solution of the present invention is first determined according to the chemical formula of the modified positive electrode material Na x-a Ca a Me 1-b Y b O 2-c Cl c The stoichiometric ratio in the is adaptively selected and adjusted. Since the Na element will be lost during the pre-sintering and calcining process, it is necessary to adjust the total excess of Na element to compensate. If the modified source does not contain the Na element, it is necessary to further select and adjust the molar amount of the sodium source based on the molar amount of the sodium source obtained according to the chemical formula, so that the total Na element is 3-8 mol% in excess of the Na molar amount in the target modified positive electrode material, and the molar amounts of the Me source and the modified source remain unchanged; if the modified source contains the Na element, the Na element can be compensated, and the molar amount of the sodium source can be adaptively selected and adjusted, so that the total Na element is 3-8 mol% in excess of the Na molar amount in the target modified positive electrode material, and the molar amounts of the Me source and the modified source remain unchanged.
[0037] As a preferred technical solution of the present invention, the modifying element includes any one of Ca, Ag, Ru or Cl, or a combination of at least two of them.
[0038] Preferably, the Ca replaces the Na site, the Ag replaces the Ni site, the Ru replaces the Mn site, and the Cl replaces the O site, preferably Ru replaces the Mn site.
[0039] In the present invention, Ru is used to replace the Mn site, which can increase the mixing entropy of cations at the atomic level, break the orderly structure of the transition metal in the transition metal layer, and thus eliminate Na + / Vacancy ordering phenomenon improves the kinetic properties of the material; the substitution of Mn position will not affect the electrochemical activity of the material itself, and can improve the stability of the material without losing capacity; Ru element can form a strong covalent Ru-O bond with O, thereby increasing the redox activity of O and improving the capacity of the material.
[0040] Preferably, the Ru source includes any one of ruthenium acetate, ruthenium trichloride or ruthenium nitrate, or a combination of at least two thereof, preferably ruthenium acetate.
[0041] Preferably, the sodium source includes any one of sodium carbonate, sodium acetate, sodium nitrate or sodium hydroxide, or a combination of at least two thereof.
[0042] Preferably, the Me source includes any one of an iron source, a nickel source, a cobalt source, a manganese source or a vanadium source, or a combination of at least two thereof, preferably a combination of a nickel source and a manganese source.
[0043] Preferably, the iron source, nickel source, cobalt source, manganese source and vanadium source each independently include any one of acetate compounds, acetate compounds or chloride compounds or a combination of at least two thereof, preferably acetate compounds.
[0044] Preferably, the nickel source includes any one of nickel chloride, nickel acetate, nickel nitrate or nickel sulfate, or a combination of at least two thereof.
[0045] Preferably, the manganese source includes any one of manganese chloride, manganese acetate, manganese nitrate or manganese sulfate, or a combination of at least two thereof.
[0046] Preferably, the solvent comprises deionized water.
[0047] Preferably, the method for preparing the mixed solution comprises: dissolving a sodium source, a Me source and a modification source in a solvent, and stirring the mixture to obtain a mixed solution.
[0048] Preferably, the stirring comprises magnetic stirring or mechanical stirring.
[0049] Preferably, the stirring speed is 300-600 rpm, such as 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm or 600 rpm, etc., preferably 400-500 rpm.
[0050] As a preferred technical solution of the present invention, the mixing includes: adding the mixed solution into the complexing agent solution.
[0051] In the preparation method of the present invention, the complexing agent solution can promote the formation of a uniform gel, thereby stabilizing metal ions and improving the uniformity of the product.
[0052] Preferably, the molar ratio of the complexing agent in the complexing agent solution to the transition metal element in the mixed solution is (0.5-1.5):1, such as 0.5:1, 0.8:1, 1.0:1, 1.2:1 or 1.5:1, etc., preferably (0.8-1.2):1.
[0053] Preferably, the mass fraction of the complexing agent solution is 6-7wt%, such as 6wt%, 6.2wt%, 6.4wt%, 6.6wt%, 6.8wt% or 7wt%.
[0054] Preferably, the complexing agent includes any one of anhydrous citric acid, ethylene glycol or ethylenediaminetetraacetic acid or a combination of at least two thereof, preferably anhydrous citric acid.
[0055] Preferably, the reaction is carried out under water bath conditions.
[0056] Preferably, the temperature of the water bath is 60-100°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, etc., preferably 75-85°C.
[0057] Preferably, the reaction is carried out with stirring.
[0058] Preferably, the reaction time is not limited and ends when a wet gel is obtained.
[0059] Preferably, the stirring comprises magnetic stirring or mechanical stirring.
[0060] Preferably, the stirring speed is 250-450 rpm, for example, 250 rpm, 280 rpm, 300 rpm, 320 rpm, 350 rpm, 380 rpm, 400 rpm, 420 rpm or 450 rpm, etc., preferably 300-400 rpm.
[0061] Preferably, the drying comprises forced air drying or vacuum drying, preferably forced air drying.
[0062] Preferably, the drying temperature is 120-180°C, such as 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, etc., preferably 140-180°C.
[0063] Preferably, the drying time is 4-10 h, such as 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., preferably 5-7 h.
[0064] As a preferred technical solution of the present invention, pre-sintering is further included after the drying and before the calcination.
[0065] Preferably, the heating rate of the pre-sintering is 2-8°C / min, such as 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or 8°C / min, and preferably 4-6°C / min.
[0066] Preferably, the sintering temperature of the pre-sintering is 300-600°C, such as 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, etc., preferably 400-500°C.
[0067] Preferably, the pre-sintering holding time is 4-8 h, such as 4 h, 5 h, 6 h, 7 h or 8 h, etc., preferably 5-7 h.
[0068] Preferably, the sintering atmosphere of the pre-sintering includes an air atmosphere or an oxygen atmosphere.
[0069] Preferably, the heating rate of the calcination is 2-8°C / min, such as 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or 8°C / min, etc., preferably 4-6°C / min.
[0070] Preferably, the sintering temperature of the calcination is 700-1100°C, such as 700°C, 800°C, 900°C, 1000°C or 1100°C, etc., preferably 850-950°C.
[0071] Preferably, the calcination holding time is 10-20 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, etc., preferably 14-16 h.
[0072] Preferably, the sintering atmosphere for calcination includes argon atmosphere, nitrogen atmosphere, air atmosphere or oxygen atmosphere, preferably argon atmosphere.
[0073] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0074] Dissolve the sodium source, Me source and modification source in deionized water, stir at a speed of 300-600 rpm at room temperature to obtain a mixed solution; add the mixed solution to a complexing agent solution with a mass fraction of 6-7wt%, stir at a speed of 250-450 rpm under 60-100°C water bath conditions to react until a wet gel is obtained, dry at 120-180°C for 4-10h, first heat to 400-500°C at a heating rate of 4-6°C / min for pre-sintering for 5-7h, and then heat to 850-950°C at a heating rate of 4-6°C / min for calcining for 14-16h to obtain the modified positive electrode material;
[0075] The modified element in the modified source and at least one element in the positive electrode material before modification conform to the diagonal rule;
[0076] Wherein, the modifying element includes any one of Ca, Ag, Ru or Cl or a combination of at least two; the Ca replaces the Na site, the Ag replaces the Ni site, the Ru replaces the Mn site, and the Cl replaces the O site; the Ru source of the Ru includes any one of ruthenium acetate, ruthenium trichloride or ruthenium nitrate or a combination of at least two; the sodium source material includes any one of sodium carbonate, sodium acetate, sodium nitrate or sodium hydroxide or a combination of at least two; the Me source includes any one of iron source, nickel source, cobalt source, manganese source or vanadium source or a combination of at least two; the iron source, nickel source, cobalt source, manganese source and vanadium source each independently include any one of acetate compound, acetate compound or chloride compound or a combination of at least two the nickel source comprises any one of nickel chloride, nickel acetate, nickel nitrate or nickel sulfate or a combination of at least two thereof; the manganese source comprises any one of manganese chloride, manganese acetate, manganese nitrate or manganese sulfate or a combination of at least two thereof; the stirring comprises magnetic stirring or mechanical stirring; the molar ratio of the complexing agent in the complexing agent solution to the transition metal element in the mixed solution as a whole is (0.5-1.5):1; the complexing agent comprises any one of anhydrous citric acid, ethylene glycol or ethylenediaminetetraacetic acid or a combination of at least two thereof; the drying comprises forced air drying or vacuum drying; the sintering atmosphere of the pre-sintering comprises air atmosphere or oxygen atmosphere; the sintering atmosphere of the calcining comprises argon atmosphere, nitrogen atmosphere, air atmosphere or oxygen atmosphere.
[0077] In a third aspect, the present invention further provides a sodium ion battery, the sodium ion battery comprising a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet arranged in sequence;
[0078] The positive electrode plate includes the modified positive electrode material as described in the first aspect, or the modified positive electrode material prepared by the preparation method as described in the second aspect.
[0079] In a fourth aspect, the present invention further provides a power device, which comprises the modified positive electrode material as described in the first aspect, or the modified positive electrode material prepared by the preparation method as described in the second aspect, or the sodium ion battery as described in the third aspect.
[0080] Compared with the prior art, the present invention has at least the following beneficial effects:
[0081] 1) The modified positive electrode material provided by the present invention is obtained by replacing at least one element in the positive electrode material before modification using the diagonal rule, that is, using an element that conforms to the diagonal rule to replace the corresponding element in the positive electrode material. Due to similar chemical properties, some diagonal elements have similar reactivity and behavior, making the substitution process easier to carry out; similar electronic structures make the diagonal elements show similar bonding modes and electron transfer characteristics when participating in chemical reactions, making it easier for them to enter specific substitution sites, and the obtained modified positive electrode material has excellent stability;
[0082] 2) The present invention adopts diagonal rule design and modifies the positive electrode material, and utilizes the interaction between elements to improve the disorder degree of cations in the modified positive electrode material, thereby suppressing the Na + / The phenomenon of orderly arrangement of vacancies, thereby improving the material capacity and cycle stability, and further enhancing the electrochemical performance of sodium-ion batteries;
[0083] 3) The modified positive electrode material obtained by substitution using the diagonal rule in the present invention has an initial discharge capacity of 130.53 mAh g after the assembled sodium ion battery. -1 The above results show that the discharge capacity after 500 cycles at 0.5C is 121.08 mAh g -1 The capacity retention rate is above 92.68%. Furthermore, when Ru replaces the Mn site, the initial discharge capacity of the sodium ion battery after assembly is as high as 145.36 mAh g -1 The discharge capacity is as high as 142.25 mAh g after 500 cycles at 0.5C. -1 , the capacity retention rate is as high as 97.86%;
[0084] 4) The preparation method provided by the present invention is simple and has a short process flow. Through the sol-gel method, a layered transition metal oxide with good density, uniform distribution and good crystallinity can be prepared. By adjusting the content of the modifying element, the modified positive electrode material component can be regulated to achieve the best electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0085] Figure 1 is a diagonal relationship diagram of Ru and Mn in the periodic table provided in Example 1 of the present invention;
[0086] Figure 2 This is a diagram of the internal structure of the modified positive electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0087] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0088] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0089] Example 1
[0090] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.33 Mn 0.52 Ru 0.15 O2, that is, Ru replaces the Mn site and both conform to the diagonal rule, and the doping amount of Ru is 0.15;
[0091] The preparation method comprises the following steps:
[0092] According to the chemical formula Na 0.67 Ni 0.33 Mn 0.52 Ru 0.15 O2, the stoichiometric ratio is 0.72:0.33:0.52:0.15. Weigh the corresponding mass of CH3COONa, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Ru(CH3COO)3, and the Na element is excessive to compensate for the Na loss during pre-sintering and calcination. Dissolve all the raw materials in 25 ml of deionized water, stir magnetically at 400 rpm for 30 min at room temperature to obtain a mixed solution, and add anhydrous citric acid into the mixed solution. The solution has a molar ratio of anhydrous citric acid to the transition metal element in the mixed solution of 1:1, and is heated in a water bath at 80°C and maintained at 350rpm magnetic stirring until a wet gel appears. The wet gel is dried at 150°C for 6h to obtain a dry gel. The obtained dry gel is fully ground, and then heated to 450°C at 5°C / min in an air atmosphere for pre-sintering for 6h, and then heated to 900°C at 5°C / min in an argon atmosphere for calcination for 15h, and then cooled to room temperature to obtain Na 0.67 Ni 0.33 Mn 0.52 Ru 0.15 O2 modified positive electrode material.
[0093] Figure 1 The diagonal relationship diagram of Ru and Mn in the periodic table of the present embodiment is shown. It can be seen from the figure that the two completely conform to the diagonal relationship.
[0094] Figure 2The internal structure diagram of the modified positive electrode material of this embodiment is shown. As can be seen from the figure, in this embodiment, Ru replaces Mn, and Ru replaces the lattice position of Mn and enters the internal structure of the positive electrode material.
[0095] Example 2
[0096] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.33 Mn 0.47 Ru 0.20 O2, Ru replaces the Mn site and both conform to the diagonal rule, and the doping amount of Ru is 0.20;
[0097] The preparation method comprises the following steps:
[0098] According to the chemical formula Na 0.67 Ni 0.33 Mn 0.47 Ru 0.20 O2, the stoichiometric ratio is 0.72:0.33:0.47:0.20. Weigh the corresponding mass of CH3COONa, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Ru(CH3COO)3, and the Na element is excessive to compensate for the Na loss during pre-sintering and calcination. Dissolve all the raw materials in 25 ml of deionized water, stir magnetically at 300 rpm for 30 min at room temperature to obtain a mixed solution, and add the mixed solution into anhydrous citric acid solution. The mixture was stirred at 450 rpm in a water bath at 60°C until a wet gel appeared. The wet gel was dried at 180°C for 4 h to obtain a dry gel. The dry gel was fully ground and then heated to 400°C at 4°C / min in an air atmosphere for pre-sintering for 7 h. The dry gel was then heated to 950°C at 6°C / min in an argon atmosphere for calcining for 14 h and then cooled to room temperature to obtain Na 0.67 Ni 0.33 Mn 0.47 Ru 0.20 O2 modified positive electrode material.
[0099] Example 3
[0100] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.33 Mn 0.62 Ru 0.05 O2, Ru replaces the Mn site, and the doping amount of Ru is 0.05;
[0101] The preparation method comprises the following steps:
[0102] According to the chemical formula Na 0.67 Ni 0.33 Mn 0.62 Ru 0.05 O2, the stoichiometric ratio is 0.72:0.33:0.62:0.05. Weigh the corresponding mass of CH3COONa, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Ru(CH3COO)3, and the Na element is excessive to compensate for the Na loss during pre-sintering and calcination. Dissolve all the raw materials in 25 ml of deionized water, stir magnetically at 600 rpm for 30 min at room temperature to obtain a mixed solution, and add the mixed solution into anhydrous citric acid solution The molar ratio of anhydrous citric acid in the anhydrous citric acid solution to the transition metal element in the mixed solution is 1.5:1, and the mixture is heated in a water bath at 100°C and maintained under magnetic stirring at 250 rpm until a wet gel appears. The wet gel is dried at 120°C for 10 h to obtain a dry gel. The obtained dry gel is fully ground, and then heated to 500°C at 6°C / min in an air atmosphere for pre-sintering for 5 h, and then heated to 850°C at 4°C / min in an argon atmosphere for calcination for 16 h, and then cooled to room temperature to obtain Na 0.67 Ni 0.33 Mn 0.62 Ru 0.05 O2 modified positive electrode material.
[0103] Example 4
[0104] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.52 Ca 0.15 Ni 0.33 Mn 0.67 O2, Ca replaces the site of Na and both conform to the diagonal rule, and the doping amount of Ca is 0.15;
[0105] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.52 Ca 0.15 Ni 0.33 Mn 0.67 O2, the stoichiometric ratio is 0.57:0.15:0.33:0.67. Weigh the corresponding masses of CH3COONa, Ca(CH3COO)2·H2O, Ni(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O, the Na element is excessive to compensate for the Na loss during pre-sintering and calcination, and the rest of the preparation method and parameters are consistent with Example 1.
[0106] Example 5
[0107] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.21 Ag 0.12 Mn 0.67 O2, Ag replaces the Ni site and the two conform to the diagonal rule, and the Ag doping amount is 0.12;
[0108] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.67 Ni 0.21 Ag 0.12 Mn 0.67 O2, the stoichiometric ratio is 0.72:0.21:0.12:0.67. Weigh the corresponding masses of CH3COONa, Ni(CH3COO)2·4H2O, CH3COOAg and Mn(CH3COO)2·4H2O, the Na element is excessive to compensate for the Na loss during pre-sintering and calcination, and the rest of the preparation method and parameters are consistent with Example 1.
[0109] Example 6
[0110] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.33 Mn 0.67 O 1.93 Cl 0.07 , Cl replaces the O site and the two conform to the diagonal rule, and the Cl doping amount is 0.07;
[0111] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.67 Ni 0.33 Mn 0.67 O 1.93 Cl 0.07 , the stoichiometric ratio is 0.65:0.33:0.67:0.07. Weigh the corresponding masses of CH3COONa, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and NaCl. The addition of NaCl brings additional sodium compensation. The other preparation methods and parameters are consistent with Example 1.
[0112] Example 7
[0113] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.52 Ca 0.15 Ni 0.33 Mn 0.52 Ru 0.15O2, Ca replaces the Na site and the two conform to the diagonal rule, Ru replaces the Mn site and the two conform to the diagonal rule, the Ca doping amount is 0.15, and the Ru doping amount is 0.15;
[0114] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.52 Ca 0.15 Ni 0.33 Mn 0.52 Ru 0.15 O2, the stoichiometric ratio is 0.57:0.15:0.33:0.52:0.15. Weigh the corresponding masses of CH3COONa, Ca(CH3COO)2·H2O, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Ru(CH3COO)3, the Na element is in excess to compensate for the Na loss during pre-sintering and calcination, and the rest of the preparation method and parameters are consistent with Example 1.
[0115] Example 8
[0116] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.52 Ca 0.15 Ni 0.21 Ag 0.12 Mn 0.52 Ru 0.15 O 1.93 Cl 0.07 , Ca replaces Na sites and both conform to the diagonal rule, Ag replaces Ni sites and both conform to the diagonal rule, Ru replaces Mn sites and both conform to the diagonal rule and Cl replaces O sites and both conform to the diagonal rule, the doping amount of Ca is 0.15, the doping amount of Ag is 0.12, the doping amount of Ru is 0.15 and the doping amount of Cl is 0.07;
[0117] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.52 Ca 0.15 Ni 0.21 Ag 0.12 Mn 0.52 Ru 0.15 O 1.93 Cl 0.07The stoichiometric ratio is 0.50:0.15:0.21:0.12:0.52:0.15:0.07. Weigh the corresponding masses of CH3COONa, Ca(CH3COO)2·H2O, Ni(CH3COO)2·4H2O, CH3COOAg, Mn(CH3COO)2·4H2O, Ru(CH3COO)3 and NaCl. The addition of NaCl brings additional sodium compensation. The other preparation methods and parameters are consistent with Example 1.
[0118] Example 9
[0119] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.33 Mn 0.42 Ru 0.25 O2, Ru replaces the Mn site, and the doping amount of Ru is 0.25;
[0120] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.67 Ni 0.33 Mn 0.45 Ru 0.22 O2, the stoichiometric ratio is 0.72:0.33:0.45:0.25, weigh the corresponding masses of CH3COONa, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Ru(CH3COO)3, the Na element is in excess to compensate for the Na loss during pre-sintering and calcination, and the rest of the preparation method and parameters are consistent with Example 1.
[0121] Example 10
[0122] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is consistent with that of Embodiment 1, that is, the chemical formula is Na 0.67 Ni 0.33 Mn 0.52 Ru 0.15 O2, Ru replaces the Mn site, and the doping amount of Ru is 0.15;
[0123] The difference between the preparation method and Example 1 is that the pre-sintering temperature is 300° C., and the other preparation methods and parameters are consistent with Example 1.
[0124] Embodiment 11
[0125] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is consistent with that of Embodiment 1, that is, the chemical formula is Na 0.67 Ni 0.33 Mn 0.52Ru 0.15 O2, Ru replaces the Mn site, and the doping amount of Ru is 0.15;
[0126] The difference between the preparation method and Example 1 is that the pre-sintering temperature is 600° C., and the other preparation methods and parameters are consistent with Example 1.
[0127] Example 12
[0128] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is consistent with that of Embodiment 1, that is, the chemical formula is Na 0.67 Ni 0.33 Mn 0.52 Ru 0.15 O2, Ru replaces the Mn site, and the doping amount of Ru is 0.15;
[0129] The difference between the preparation method and Example 1 is that the calcination temperature is 700° C., and the other preparation methods and parameters are consistent with Example 1.
[0130] Embodiment 13
[0131] This embodiment provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is consistent with that of Embodiment 1, that is, the chemical formula is Na 0.67 Ni 0.33 Mn 0.52 Ru 0.15 O2, Ru replaces the Mn site, and the doping amount of Ru is 0.15;
[0132] The difference between the preparation method and Example 1 is that the calcination temperature is 1100° C., and the other preparation methods and parameters are consistent with Example 1.
[0133] Comparative Example 1
[0134] This comparative example provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.33 Mn 0.52 Fe 0.15 O2, that is, Fe replaces the site of Mn and the two do not conform to the diagonal rule, and the doping amount of Fe is 0.15;
[0135] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.67 Ni 0.33 Mn 0.52 Fe 0.15O2, the stoichiometric ratio is 0.72:0.33:0.52:0.15. Weigh the corresponding masses of CH3COONa, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Fe(CH3COO)3, the Na element is in excess to compensate for the Na loss during pre-sintering and calcination, and the rest of the preparation method and parameters are consistent with Example 1.
[0136] Comparative Example 2
[0137] This comparative example provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.33 Mn 0.52 Co 0.15 O2, that is, Co replaces the site of Mn and the two do not conform to the diagonal rule, and the doping amount of Co is 0.15;
[0138] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.67 Ni 0.33 Mn 0.52 Co 0.15 O2, the stoichiometric ratio is 0.72:0.33:0.52:0.15. Weigh the corresponding masses of CH3COONa, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Co(CH3COO)2·4H2O, the Na element is in excess to compensate for the Na loss during pre-sintering and calcination, and the rest of the preparation method and parameters are consistent with Example 1.
[0139] Comparative Example 3
[0140] This comparative example provides a modified positive electrode material and a preparation method thereof. The chemical formula of the modified positive electrode material is Na 0.67 Ni 0.33 Mn 0.52 R 0.15 O2, that is, Rh replaces the site of Mn and the two do not conform to the diagonal rule, and the doping amount of Rh is 0.15;
[0141] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.67 Ni 0.33 Mn 0.52 R 0.15 O2, the stoichiometric ratio is 0.72:0.33:0.52:0.15. Weigh the corresponding masses of CH3COONa, Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Rh(CH3COO)3, the Na element is in excess to compensate for the Na loss during pre-sintering and calcination, and the rest of the preparation method and parameters are consistent with Example 1.
[0142] Comparative Example 4
[0143] This comparative example provides a positive electrode material and a preparation method thereof. The chemical formula of the positive electrode material is Na 0.67 Ni 0.33 Mn 0.67 O2, i.e., without any metal substitution;
[0144] The difference between the preparation method and Example 1 is that according to the chemical formula Na 0.67 Ni 0.33 Mn 0.67 O2, the stoichiometric ratio is 0.72:0.33:0.67. Weigh the corresponding masses of CH3COONa, Ni(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O, the Na element is excessive to compensate for the Na loss during pre-sintering and calcination, and the rest of the preparation method and parameters are consistent with Example 1.
[0145] The modified positive electrode materials prepared in Examples 1-13 and Comparative Examples 1-3, and the positive electrode material prepared in Comparative Example 4 were used as positive electrode active materials, and were uniformly mixed with superconducting carbon black (Super-P) and polyvinylidene fluoride (PVDF) at a mass ratio of 7:2:1, and N-methylpyrrolidone (NMP) was added to prepare a positive electrode slurry, which was uniformly coated on an aluminum foil, dried in a blast dryer at 60° C. for 2 h, and then transferred to a vacuum dryer at 120° C. for vacuum drying for 12 h, and then cut into discs with a diameter of 12 mm to obtain positive electrode sheets; a metal sodium sheet was cut into discs with a diameter of 10 mm to obtain a negative electrode sheet; a glass fiber separator was cut into discs with a diameter of 16 mm;
[0146] 1M NaClO4 was dissolved in propylene carbonate (PC), and 5% fluoroethylene carbonate (FEC) was added as an additive to obtain an electrolyte;
[0147] The positive electrode sheet, electrolyte, glass fiber separator, and negative electrode sheet are stacked in sequence in a 2032 button battery shell to assemble a button battery.
[0148] The battery was charged and discharged at a constant current in the voltage range of 2.0-4.4V and a current density of 0.5C, and the battery's first cycle discharge capacity and discharge capacity after 500 cycles were tested, and the capacity retention rate was calculated. Specific data are shown in Table 1.
[0149] Table 1
[0150]
[0151]
[0152] The test results show that:
[0153] (1) It can be seen from Examples 1 to 13 that the present invention modifies the positive electrode material by using the diagonal rule. The similar chemical properties between the diagonal elements make them have similar reactivity and behavior as well as similar bonding mode and electron transfer characteristics, making it easier to replace specific sites, thereby effectively improving the electrochemical performance of the modified positive electrode material.
[0154] In Example 1-3, Ru was used to replace the Mn site. After the modified positive electrode material was assembled into a battery, the first cycle discharge capacity was as high as 145.36 mAh g -1 The discharge capacity is as high as 142.25 mAh g after 500 cycles at 0.5C. -1 The capacity retention rate is as high as 97.86%, which shows the characteristics of high capacity and high cycle stability. The use of Ru to replace Mn can increase the mixing entropy of cations at the atomic level, break the ordered structure of transition metals in the transition metal layer, and thus eliminate Na + / Vacancy ordering phenomenon improves the kinetic performance of the modified cathode material; on the other hand, the formation of strong covalent Ru-O bonds can increase the redox activity of O and improve the capacity of the modified cathode material;
[0155] In Example 4, Ca is used to replace the Na site. Under the premise of satisfying the diagonal rule, the cation disorder of the modified positive electrode material can be improved, and the Na + / vacancy ordering phenomenon. In addition, replacing the Na site with Ca can also provide a larger alkali metal interlayer spacing through a steric effect, thereby increasing the Na + Migration rate, improving the rate performance of modified cathode materials;
[0156] In Example 5, Ag is used to replace Ni sites. Ag and Ni have similar chemical properties. Using Ag to replace Ni sites can not only improve the cation disorder of the modified positive electrode material, but also significantly improve the conductivity of the modified positive electrode material, so that the modified positive electrode material has excellent rate performance and cycle stability;
[0157] In Example 6, O is used to replace the Cl site. O and Cl are located in the diagonal position in the periodic table, have similar electronegativity, and exhibit similar bonding mode and electron transfer characteristics when participating in chemical reactions. A trace amount of Cl substitution can expand the interlayer spacing, accelerate charge transfer, and enhance the structural stability of the material, thereby improving the electrochemical properties of the modified positive electrode material;
[0158] Examples 7 and 8 use multi-site diagonal element substitution and utilize the synergistic effect between different substitution sites to further improve the structural stability of the modified positive electrode material. The resulting modified positive electrode material exhibits excellent capacity retention.
[0159] (2) It can be seen from Examples 1 and 9 that limiting the doping amount to 0.01-0.2 can make the modified positive electrode material itself have higher stability. Excessive element substitution will affect the stable crystal structure of the modified positive electrode material itself, because the optimized lattice parameters are excessively changed, thereby interfering with the diffusion path of sodium ions, causing their transmission to be blocked, making it more likely to cause structural collapse during the charge and discharge process, and exhibiting poor electrochemical performance. Too little element substitution cannot fully exert the role of the replacing element, and has no obvious improvement effect on the electrochemical performance of the modified positive electrode material.
[0160] (3) It can be seen from Example 1 and Examples 10-11 that limiting the pre-sintering temperature to 400-500°C can maximize the thermal decomposition transformation of the precursor of the modified positive electrode material, and the prepared modified positive electrode material has excellent electrochemical properties. The modified positive electrode material with a pre-sintering temperature that is too low cannot maximize the thermal decomposition transformation of the precursor, the adsorbed water and crystallization water are not fully released, the citric acid and acetate are not completely decomposed, and the doping elements cannot be fully diffused and evenly distributed, thereby affecting the electrochemical properties of the modified positive electrode material; the modified positive electrode material with a pre-sintering temperature that is too high will cause excessive thermal decomposition of the precursor, trigger unnecessary chemical reactions, produce impurity phases, and also cause a certain element loss of the doping element, affecting the electrochemical properties of the modified positive electrode material.
[0161] It can be seen from Examples 1 and 12-13 that limiting the calcination temperature to 850-950°C can make the modified positive electrode material have better initial capacity and cycle stability. If the calcination temperature is too low, the crystallization of the modified positive electrode material is not perfect, the distance between particles is large, and the Na + The diffusion path is too long, which affects the kinetic performance of the modified positive electrode material, and is easy to generate impurities, which is not conducive to the formation of a pure phase P2 structure. The modified positive electrode material exhibits a lower initial capacity and poor cycle stability. The calcination temperature is too high, the spacing between particles is too small, and particles are prone to agglomeration, resulting in poor electrochemical performance of the modified positive electrode material.
[0162] (4) It can be seen from Comparative Examples 1 to 4 that non-diagonal elements are used to replace Mn in Comparative Examples 1 to 3, and the positive electrode material in Comparative Example 4 is not replaced by any metal element, that is, it is not modified;
[0163] Comparative Examples 1 to 3 use non-diagonal elements to modify the positive electrode materials. Although the modified positive electrode materials substituted with non-diagonal elements show certain performance improvement on the basis of no metal element substitution in Comparative Example 4, the degree of performance improvement is limited (compared with Examples 1 to 13);
[0164] Furthermore, elements that conform to the diagonal rule can maximize the mixing entropy of the material relative to other elements. On the one hand, similar chemical properties make some diagonal elements have similar reactivity and behavior, which makes the substitution process easier, thereby increasing the disorder of the system and leading to an increase in the mixing entropy; on the other hand, similar electronic structures make the diagonal elements exhibit similar bonding methods and electron transfer characteristics when participating in chemical reactions, and can be combined or replaced with each other in a variety of ways, making it easier for them to enter specific substitution sites. In addition, since the properties of the elements on the diagonal are neither completely the same nor similar, the interactions between them are more complex than those between non-diagonal elements. This complex interaction makes the arrangement of atoms and the distribution of electrons in the system more diverse after doping and mixing, showing a trend of maximizing the mixing entropy increase. This trend of mixing entropy increase effectively suppresses the unfavorable Na+ / Na+ events that occur during the charge and discharge process. + The orderly arrangement of vacancies / spaces increases the capacity and cycle stability of the modified cathode material, further improving the electrochemical performance of sodium-ion batteries.
[0165] In summary, the present invention uses the diagonal rule to replace at least one element in the positive electrode material before modification, and the modified positive electrode material obtained can improve the disorder degree of cations in the positive electrode material, maximize the mixing entropy of the material, and inhibit the Na + / Vacancy ordered arrangement phenomenon and irreversible phase transition phenomenon; in addition, the preparation method of the present invention is simple, and the sodium ion battery prepared by using the modified positive electrode material has excellent cycle stability and rate performance.
[0166] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A modified positive electrode material, It is characterized in that The modified positive electrode material is a layered transition metal oxide material; The modified positive electrode material is obtained by replacing at least one element in the positive electrode material before modification using the diagonal rule.
2. The modified positive electrode material according to claim 1, It is characterized in that The chemical formula of the positive electrode material before modification includes Na x MeO 2 , wherein 0<x≤1, and the Me comprises any one or a combination of at least two transition metal elements; Preferably, the diagonal rule includes replacing the Na position with a Ca element located adjacent to the lower right corner of the Na element; and / or replacing at least one element in the Me position with an element located adjacent to the lower right corner of the Me element; and / or replacing the O position with a Cl element located adjacent to the lower right corner of the O element; Preferably, the chemical formula of the modified positive electrode material includes Na x-a Ca a Me 1-b Y b O 2-c Cl c , where 0<x≤1, 0≤a<x, 0≤b<1, 0≤c<2 and a, b, c are not 0 at the same time, Y and Me meet the diagonal rule; Preferably, 0.5<x≤0.7; Preferably, 0<a≤0.5, preferably 0.01≤a≤0.2; Preferably, 0<b≤0.5, preferably 0.01≤b≤0.2; Preferably, 0<c≤0.5, preferably 0.01≤c≤0.2; Preferably, the Me includes any one of Fe, Ni, Co, Mn or V or a combination of at least two thereof, preferably a combination of Ni and Mn; Preferably, Y includes any one of Rh, Ag, Pd, Ru or Mo or a combination of at least two thereof, preferably a combination of Ag and Ru.
3. A method for preparing the modified positive electrode material according to claim 1 or 2, It is characterized in that The preparation method comprises the following steps: The positive electrode material before modification is reacted with the modification source in situ to obtain a modified positive electrode material; The modified element in the modified source and at least one element in the positive electrode material before modification conform to the diagonal rule.
4. The preparation method according to claim 3, It is characterized in that The reaction method includes a sol-gel method, a solid phase reaction method or a coprecipitation method, preferably a sol-gel method; Preferably, the sol-gel method comprises the following steps: The mixed solution and the complexing agent solution are mixed and reacted to obtain a wet gel, and after drying and calcining, the modified positive electrode material is obtained; The mixed solution comprises a sodium source, a Me source, a modification source and a solvent.
5. The preparation method according to claim 4, It is characterized in that The modifying element includes any one of Ca, Ag, Ru or Cl or a combination of at least two thereof; Preferably, the Ca replaces the Na site, the Ag replaces the Ni site, the Ru replaces the Mn site, and the Cl replaces the O site, preferably Ru replaces the Mn site; Preferably, the Ru source includes any one of ruthenium acetate, ruthenium trichloride or ruthenium nitrate, or a combination of at least two thereof, preferably ruthenium acetate; Preferably, the Me source includes any one of an iron source, a nickel source, a cobalt source, a manganese source or a vanadium source, or a combination of at least two thereof, preferably a combination of a nickel source and a manganese source; Preferably, the iron source, nickel source, cobalt source, manganese source and vanadium source each independently include any one of acetate compounds, acetate compounds or chloride compounds or a combination of at least two thereof, preferably acetate compounds.
6. The preparation method according to claim 4 or 5, It is characterized in that The mixing comprises: adding the mixed solution into the complexing agent solution; Preferably, the molar ratio of the complexing agent in the complexing agent solution to the transition metal element in the mixed solution is (0.5-1.5):1, preferably (0.8-1.2):1; Preferably, the complexing agent comprises any one of anhydrous citric acid, ethylene glycol or ethylenediaminetetraacetic acid or a combination of at least two thereof, preferably anhydrous citric acid; Preferably, the reaction is carried out under water bath conditions; Preferably, the temperature of the water bath is 60-100°C, preferably 75-85°C; Preferably, the reaction is accompanied by stirring; Preferably, the stirring speed is 250-450 rpm, preferably 300-400 rpm.
7. The preparation method according to any one of claims 4 to 6, It is characterized in that After the drying, and before the calcination, pre-sintering is also included; Preferably, the heating rate of the pre-sintering is 2-8°C / min, preferably 4-6°C / min; Preferably, the sintering temperature of the pre-sintering is 300-600°C, preferably 400-500°C; Preferably, the pre-sintering holding time is 4-8h, preferably 5-7h; Preferably, the heating rate of the calcination is 2-8°C / min, preferably 4-6°C / min; Preferably, the sintering temperature of the calcination is 700-1100°C, preferably 850-950°C; Preferably, the calcination holding time is 10-20h, preferably 14-16h; Preferably, the sintering atmosphere for calcination includes argon atmosphere, nitrogen atmosphere, air atmosphere or oxygen atmosphere, preferably argon atmosphere.
8. The preparation method according to any one of claims 3 to 7, It is characterized in that The preparation method comprises the following steps: Dissolve the sodium source, Me source and modification source in deionized water, stir evenly at room temperature at a speed of 300-600 rpm to obtain a mixed solution; add the mixed solution to a complexing agent solution with a mass fraction of 6-7wt%, stir at a speed of 250-450 rpm under 60-100°C water bath conditions to react until a wet gel is obtained, dry at 120-180°C for 4-10h, first heat to 400-500°C at a heating rate of 4-6°C / min for pre-sintering for 5-7h, and then heat to 850-950°C at a heating rate of 4-6°C / min for calcining for 14-16h to obtain a modified positive electrode material; The modified element in the modified source and at least one element in the positive electrode material before modification conform to the diagonal rule; Wherein, the modifying element includes any one of Ca, Ag, Ru or Cl or a combination of at least two; the Ca replaces the Na site, the Ag replaces the Ni site, the Ru replaces the Mn site, and the Cl replaces the O site; the Ru source of the Ru includes any one of ruthenium acetate, ruthenium trichloride or ruthenium nitrate or a combination of at least two; the sodium source material includes any one of sodium carbonate, sodium acetate, sodium nitrate or sodium hydroxide or a combination of at least two; the Me source includes any one of iron source, nickel source, cobalt source, manganese source or vanadium source or a combination of at least two; the iron source, nickel source, cobalt source, manganese source and vanadium source each independently include any one of acetate compound, acetate compound or chloride compound or a combination of at least two the nickel source comprises any one of nickel chloride, nickel acetate, nickel nitrate or nickel sulfate or a combination of at least two thereof; the manganese source comprises any one of manganese chloride, manganese acetate, manganese nitrate or manganese sulfate or a combination of at least two thereof; the stirring comprises magnetic stirring or mechanical stirring; the molar ratio of the complexing agent in the complexing agent solution to the transition metal element in the mixed solution as a whole is (0.5-1.5):1; the complexing agent comprises any one of anhydrous citric acid, ethylene glycol or ethylenediaminetetraacetic acid or a combination of at least two thereof; the drying comprises forced air drying or vacuum drying; the sintering atmosphere of the pre-sintering comprises air atmosphere or oxygen atmosphere; the sintering atmosphere of the calcining comprises argon atmosphere, nitrogen atmosphere, air atmosphere or oxygen atmosphere.
9. A sodium ion battery, It is characterized in that The sodium ion battery comprises a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet arranged in sequence; The positive electrode plate comprises the modified positive electrode material as described in claim 1 or 2, or the modified positive electrode material prepared by the preparation method as described in any one of claims 3-8.
10. A power device, It is characterized in that The power device comprises the modified positive electrode material as described in claim 1 or 2, or the modified positive electrode material prepared by the preparation method according to any one of claims 3 to 8, or the sodium ion battery according to claim 9.
Citation Information
Patent Citations
Titanium-doped sodium ion battery positive electrode layered oxide material as well as preparation method and application thereof
CN116259743A
Layered oxide positive electrode material, sodium ion battery and preparation method
CN117613255A
Gradient-doped oxide positive electrode material for sodium ion battery and preparation method of gradient-doped oxide positive electrode material
CN117878324A
